Prevalence Of Antibodies Against Persistent Production Limiting Infections In Ruminants In India (Applied Biological Research, 2017)
The present study was aimed to screen ruminants for the prevalence of  antibodies against four major persistent production-limiting infections in  different agro-climatic zones of West Bengal (India). Two-hundred and twenty  (n = 220) serum samples from cattle (n = 74), goats (n = 109) and sheep (n =  37) were collected from four agro-climatic zones of West Bengal. In present study, IBR antibodies was detected in 11 sera samples (11/74, 14.8%) collected from cattle only. Antibodies against BVD was detected in sera samples collected from three sheep (3/37, 8.1%) and one cattle (1/74, 1.3%). The MAP antibodies were detected in sera samples collected from three goats (3/109, 2.7%), two sheep (2/37, 5.4%) and one cattle (1/74, 1.3%). The antibodies against Chlamydophila abortus was confirmed in sera samples collected from two cattle (2/74, 2.6%). The study revealed lower seroprevalence of four major persistent and production limiting microbial infection in ruminants in Bengal.
Keywords: BVD; Chlamydophila; ELISA; India; MAP; West Bengal